Impact of field roughness and power losses, turbulence intensity on electricity production for an onshore wind farm - Bedri Dragusha; Bukurije Hoxha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
When designing a power generation project from a different source, and in our case study, wind, when calculating the annual energy produced, it is necessary to define and calculate the losses incurred in the system.  The main cause of losses in a wind park is due to the oscillations caused by the turbulence of the air around the turbine because of roughness of terrain. The paper describes two methods of estimating turbulence intensity: one based on the mean and standard deviation (SD) of wind speed from the nacelle anemometer, the other from mean power output and its SD. These analyses are very important for understanding the fatigue and mechanical stress on the wind turbines. Then significance of the site ruggedness index (RIX) and the associated performance indicator (ΔRIX) are confirmed for terrain and the consequences of applying WAsP outside its operating envelope are quantified.